Heart rate recovery after six-minute walk test predicts pulmonary hypertension in patients with idiopathic pulmonary fibrosis - SWIGRIS, Jeffrey J. (2011)
BACKGROUND AND OBJECTIVE: In patients with IPF, we sought to validate that abnormal heart rate recovery at 1 min (HRR1) after six-minute walk test (6MWT) predicts mortality and to explore the relationship between abnormal HRR1 and pulmonary hypertension (PH). METHODS: We identified IPF patients who performed a 6MWT as part of their clinical evaluation between 2006 and 2009 and were followed to lung transplantation or death. Right heart catheterization (RHC) data were collated and analysed for the subgroup who had this procedure. RESULTS: There were 160 subjects who qualified for the survival analysis, and those with an abnormal HRR1 had worse survival than subjects with normal HRR1 (log-rank P = 0.01). Eighty-two subjects had a right heart catheter (RHC); among them, abnormal HRR1 was associated with RHC-confirmed PH (χ(2) = 4.83, P = 0.03) and had a sensitivity, specificity, positive predictive value and negative predictive value of 52%, 74%, 41% and 82%, respectively, for PH. In bivariate and multivariable analyses, abnormal HRR1 appeared to be the strongest predictor of RHC-confirmed PH (odds ratio (OR) = 4.0, 95% CI: 1.17–13.69, P = 0.02 in the multivariable analysis). CONCLUSIONS: This study adds to data that support the validity of abnormal HRR1 as a predictor of mortality and of RHC-confirmed PH in IPF. Research is needed to further investigate the link between abnormal HRR1 and PH and to elucidate heart–lung interactions at work during exercise and recovery in patients with IPF.